Interobserver Variability in the Diagnosis of High-Grade Prostatic Intraepithelial Neoplasia in a Tertiary Hospital in Northern Jordan - Najla Aldaoud; Amer Hallak; Nour Abdo; Samir Al Bashir; Noor Marji; Ashley Graboski-Bauer (SAGE Publishing, 2020)
Prostate intraepithelial neoplasia is described as a precursor lesion to prostatic adenocarcinoma. High-grade prostate intraepithelial neoplasia (HGPIN) is classified as both grade 2 and 3 prostate intraepithelial neoplasia due to inconsistency between pathologists' findings. In our study, we assessed the interobserver variability in the diagnosis of HGPIN among genitourinary and nongenitourinary pathologists. All cases with prostate adenocarcinoma diagnosis on needle core biopsy, radical prostatectomy, and transurethral resection of prostate (TURP) between the years 2005 and 2014 were included. In total, 191 prostate cancer cases were included: 109 needle core biopsies, 45 radical prostatectomies, and 37 TURP. All were independently reviewed by 2 urologic pathologists for the presence of HGPIN. High-grade prostate intraepithelial neoplasia was diagnosed in 65 cases (34%), among which the lesion was recognized by the reporting pathologists in 36 (55%) of the cases and was missed in 29 (45%) of the cases with a κ coefficient of 0.53. There was a moderate interobserver agreement in the diagnosis of HGPIN. Consultation with genitourinary pathologist can improve HGPIN diagnosis.